Progerin sequestration of PCNA promotes replication fork collapse and mislocalization of XPA in laminopathy‐related progeroid syndromes. Issue 9 (19th September 2017) - Hilton, Benjamin A.; Liu, Ji; Cartwright, Brian M.; Liu, Yiyong; Breitman, Maya; Wang, Youjie; Jones, Rowdy; Tang, Hui; Rusinol, Antonio; Musich, Phillip R.; Zou, Yue
ABSTRACT: Hutchinson‐Gilford progeria syndrome (HGPS) is a rare genetic disorder that is caused by a point mutation in the LMNA gene, resulting in production of a truncated farnesylated‐prelamin A protein (progerin). We previously reported that XPA mislocalized to the progerin‐induced DNA double‐strand break (DSB) sites, blocking DSB repair, which led to DSB accumulation, DNA damage responses, and early replication arrest in HGPS. In this study, the XPA mislocalization to DSBs occurred at stalled or collapsed replication forks, concurrent with a significant loss of PCNA at the forks, whereas PCNA efficiently bound to progerin. This PCNA sequestration likely exposed ds‐ssDNA junctions at replication forks for XPA binding. Depletion of XPA or progerin each significantly restored PCNA at replication forks. Our results suggest that although PCNA is much more competitive than XPA in binding replication forks, PCNA sequestration by progerin may shift the equilibrium to favor XPA binding. Furthermore, we demonstrated that progerin‐induced apoptosis could be rescued by XPA, suggesting that XPA‐replication fork binding may prevent apoptosis in HGPS cells. Our results propose a mechanism for progerin‐induced genome instability and accelerated replicative senescence in HGPS.—Hilton, B. A., Liu, J., Cartwright, B. M., Liu, Y., Breitman, M., Wang, Y., Jones, R., Tang, H., Rusinol, A., Musich, P. R., Zou, Y. Progerin sequestration of PCNA promotes replication fork collapse and mislocalization of XPA in laminopathy‐related progeroid syndromes. FASEB J. 31, 3882–3893 (2017). www.fasebj.org —Hilton, Benjamin A., Liu, Ji, Cartwright, Brian M., Liu, Yiyong, Breitman, Maya, Wang, Youjie, Jones, Rowdy, Tang, Hui, Rusinol, Antonio, Musich, Phillip R., Zou, Yue Progerin sequestration of PCNA promotes replication fork collapse and mislocalization of XPA in laminopathy‐related progeroid syndromes. FASEB J. 31, 3882–3893 (2017)